Konsentrasi Pembunuhan pada Lokasi Mikro: Analisis Kriminologi Komparatif atas Risiko Kematian di Berbagai Kawasan Dunia - Zul Khaidir Kadir (Media Hukum Indonesia (MHI), 2026)
This article examines the spatial concentration of homicide at micro-places across world regions by treating lethal risk as a problem of place, governance, and data quality. Homicide rates per 100,000 population remain useful for comparing the burden of violence across territories, but they do not explain why deaths repeatedly occur in particular small locations. Such risk may appear on street segments, transport nodes, night-time economy sites, markets, parking areas, or private spaces such as the home. Using a place-based comparative analytical design, the article explores how place characteristics, environmental risk, and spatial governance shape homicide hot spots. Homicide concentration does not emerge from places that are inherently dangerous. Risk is produced when recurring conflict intersects with weak guardianship, poor visibility, accessible escape routes, weapon availability, and delayed assistance. Cross-regional comparison suggests that these mechanisms operate unevenly. In some cities, hot spots are tied to territorial control and illegal assets. In others, lethal risk is more closely linked to night-time economies, informal urban spaces, closed domestic relations, or imprecise location recording. The article contributes to comparative homicide studies by moving beyond aggregate rates and by linking micro-place dynamics to urban governance and regional variation. Micro-places are treated as event sites, cities as arenas of surveillance and service delivery, and world regions as settings where lethal risk is recorded, governed, displaced, or allowed to persist in different ways.